Abnormal Return Saham Sektor Teknologi dan Keuangan: Studi Komparatif BEI dan SET Thailand saat Pandemi COVID-19 - Martono, Cyrillius (Jurnal EMT KITA, 2026)
This study examines the presence of significant positive abnormal returns in the technology and financial sectors on the Indonesia Stock Exchange (IDX) and the Stock Exchange of Thailand (SET) during the COVID-19 pandemic. Using an event study methodology with a 360 trading days, namely March 2, 2020 (the date of the announcement of the first case of COVID-19 in Indonesia, t=0), with a sample size of 35 shares on the IDX (15 technology, 20 finance) and 30 shares on the SET (12 technology, 18 finance), this study measures the market's response to the pandemic shock. A one-sample t-test reveals significant positive abnormal returns in both sectors and markets, with the Indonesian technology sector recording the highest abnormal return. Paired t-tests confirm significant differences between the technology and financial sectors within the same market; in contrast, independent t-tests show no significant differences in abnormal returns across markets for the same sector. These findings indicate that the technology sector demonstrates greater resilience and growth potential than the financial sector, with relatively comparable performance across these major ASEAN markets. This study contributes to the literature on semi-strong-form market efficiency and signaling theory by addressing gaps in the literature on emerging ASEAN markets during a prolonged crisis and by providing strategic implications for investors and regulators in managing risks and making post-pandemic investment decisions. Additionally, the study highlights the need for enhanced regional policy collaboration to strengthen capital market stability in the ASEAN region.